2022
DOI: 10.1080/00218839.2022.2113329
|View full text |Cite
|
Sign up to set email alerts
|

Honey bee colony loss rates in 37 countries using the COLOSS survey for winter 2019–2020: the combined effects of operation size, migration and queen replacement

Abstract: This article presents managed honey bee colony loss rates over winter 2019/20 resulting from using the standardised COLOSS questionnaire in 37 countries. Six countries were from outside Europe, including, for the first time in this series of articles, New Zealand. The 30,491 beekeepers outside New Zealand reported 4.5% of colonies with unsolvable queen problems, 11.1% of colonies dead after winter and 2.6% lost through natural disaster. This gave an overall colony winter loss rate of 18.1%, higher than in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 8 publications
2
45
0
Order By: Relevance
“…Most regions followed the same pattern of queen replacement ( Supplementary Table S2 ). Previous work has identified that queen replacement has a direct impact on hive losses [ 40 , 41 , 48 ]. Therefore, we investigated whether the loss rate per beekeeper correlated with their respective queen replacement rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most regions followed the same pattern of queen replacement ( Supplementary Table S2 ). Previous work has identified that queen replacement has a direct impact on hive losses [ 40 , 41 , 48 ]. Therefore, we investigated whether the loss rate per beekeeper correlated with their respective queen replacement rate.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to address bee issues, as well as the compartmentation of existing research, in 2008, the international scientific research association “COLOSS” (Prevention of COlony LOSSes) was founded, to connect honey bee experts, reinforce their scientific collaboration and improve the well-being of honey bees on a global scale [ 18 , 37 ]. One of its core activities since the very start [ 38 ] has been the Citizen Science “Colony Losses Monitoring” project [ 39 ], which is currently active in many countries from Europe and the rest of the world [ 40 , 41 , 42 ]. The objective of this group effort is to collect and report internationally comparable data [ 43 ] concerning colony mortality during winter—the most critical season for colony losses for most European countries [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, A. mellifera is one of the most commonly managed insects in the world. The large-scale losses of managed colonies reported in recent times in the Northern Hemisphere potentially threaten the services honey bees provide ( Decourtye et al, 2019 , Gray, 2022 , Kulhanek et al, 2017 , Liu et al, 2016 , Neumann and Carreck, 2010 , Potts et al, 2010 , Steinhauer et al, 2018 ). Honey bee health has thus become a major concern for scientists, policy-makers, beekeepers and the public ( Evans and Schwarz, 2011 , Moritz et al, 2010 , Smith et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The western honey bee, Apis mellifera L. (Hymenoptera: Apidae), is an important pollinator in natural and agricultural ecosystems (Potts et al, 2010;Garibaldi et al, 2017;Khalifa et al, 2021). Significant bee colony losses have been observed worldwide in recent decades (Gray et al, 2019(Gray et al, , 2022. This issue has drawn particular attention to identifying factors that negatively affect honey bee health, and it is believed that poor nutrition may be one of them.…”
Section: Introductionmentioning
confidence: 99%